Heavy-hole and light-hole excitons in nonlinear absorption spectra of colloidal nanoplatelets. (September 2019) - Smirnov, A.M.; Mantsevich, V.N.; Smirnov, D.S.; Golinskaya, A.D.; Kozlova, M.V.; Saidzhonov, B.M.; Dneprovskii, V.S.; Vasiliev, R.B.
Abstract: We study the nonlinear optical response of CdSe/CdS nanoplatelets (NPLs) in the vicinity of heavy hole (hh) and light hole (lh) exciton resonances by means of the two color pump-probe technique. The population of hh and lh excitonic states leads to the decrease of the light absorption at both resonances under resonant excitation of one of them. Increase of the pump power leads to the saturation of the absorption. This effect allows us to estimate the exciton total lifetime. Highlights: Nonlinear optical response of CdSe/CdS nanoplatelets in the vicinity of heavy (light) hole exciton resonances. Two color pump-probe technique is applied to study quasi steady state. We revealed small ratio of exciton scattering times to higher and lower energies. Saturation of differential transmission was also observed.